2017
DOI: 10.2308/jeta-51911
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain: Emergent Industry Adoption and Implications for Accounting

Abstract: Blockchain is a distributed ledger technology poised to transform the accounting practice. In this paper, we provide an initial examination of the technology itself and discuss the associated opportunities and limitations. We also present an overview of the current blockchain-related practices in large accounting firms and trace significant milestones in this technology's emergence. Finally, we discuss some potential areas that future research could address.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
214
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 239 publications
(239 citation statements)
references
References 7 publications
3
214
0
1
Order By: Relevance
“…By combining the processing of transactions with the recording and reconciling of those transactions, BT introduces substantial efficiencies (EY ; ACCA ; CPA and AICPA ; Kokina et al. ; PwC , ). Precisely, the need for entering and reconciling accounting data in multiple databases is eliminated, whereby time is saved and the risk of human error is substantially reduced (Kokina et al.…”
Section: Results From the Thematic Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…By combining the processing of transactions with the recording and reconciling of those transactions, BT introduces substantial efficiencies (EY ; ACCA ; CPA and AICPA ; Kokina et al. ; PwC , ). Precisely, the need for entering and reconciling accounting data in multiple databases is eliminated, whereby time is saved and the risk of human error is substantially reduced (Kokina et al.…”
Section: Results From the Thematic Analysismentioning
confidence: 99%
“…Precisely, the need for entering and reconciling accounting data in multiple databases is eliminated, whereby time is saved and the risk of human error is substantially reduced (Kokina et al. ).…”
Section: Results From the Thematic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, Gencer () explained that scalability refers to blockchain technology's ability to meet a targeted level of throughput (processing output) while minimizing latency (the time interval or delay when a system component is waiting for another system component to perform a task). Kokina, Mancha, and Pachamanova () reported that Visa, Inc. processes 4,000 transactions per second. By contrast, because blockchain technology is computationally intensive, Ethereum (an open‐source public blockchain designed to support decentralized applications such as smart contracts) processes only about 20 transactions per second while bitcoin (another public blockchain application) can process only about seven transactions per second (Rosic, ).…”
Section: Barriers To Blockchain Adoptionmentioning
confidence: 99%